Marketing Communication Strategy On Customer Loyalty - Dandi Wijaya; Aslinda Aslinda; Muh Luthfi Siraj (Public Resource Innovation Management and Excellence, 2024)
Marketing communication is one of the techniques used by a company to inform, promote and introduce their products to the public and get customers (customers) so that people can be loyal to the products offered. This study discusses the marketing communication strategy on customer loyalty at PT. Bank Bri Unit Wholesale Raya Makassar. This type of research is descriptive research using a quantitative research design. In this study, the researcher tried to ascertain the high level of correlation of the marketing communication strategy variables on customer loyalty. This study used a descriptive method, data collection was carried out by observation, questionnaires, and documentation and analyzed using statistical formulas which were calculated using SPSS assistance. From the results of data processing for the marketing communication strategy variable obtained a value of 81.16 percent so it can be concluded that the marketing communication strategy at PT. Bank Bri Unit Borong Raya Makassar is in the very good category. The results of data processing for the customer loyalty variable obtained a value of 78.68 percent, it can be concluded that customer loyalty at PT. Bank Bri Unit Borong Raya Makassar is in the good category. From the results of the correlation coefficient analysis, it is obtained that the correlation coefficient is = 0.563, so it can be concluded that the marketing communication strategy is correlated with a moderate level of customer loyalty at PT. Bank Bri Unit Wholesale Raya Makassar.